Dinamika Interdependensi Bilateral Indonesia-Jerman dalam Implementasi Program Ausbildung - Tsabitha, Camilla (Jurnal Studi Diplomasi dan Keamanan, 2026)
The lack of skilled workers in Germany, the challenge of demographic bonuses in Indonesia, and the flow of mobility that has the potential to trigger brain drain from complex and asymmetric problems in the Indonesia- Germany Ausbildung program. This research aims to map complex interdependence patterns, assess the distribution of benefits or risks, and formulate policy options so that vocational mobility contributes to Indonesia’s brain gain. Qualitative-descriptive methods based on literature studies are used to assess motives, policy actors, and distribution of benefits and risks. The findings suggest an asymmetrical state of interdependence with Germany that benefits through the supply of skilled labor and the strengthening of the innovation ecosystem. On the other hand, Indonesia has access to international standardized training, legal work mobility, and mitigation, but faces the risk of permanent migration due to weak recognition and reintegration. Recommendations include recognition of overseas certification, talent circulation schemes, fair recruitment, enterpreneurship incentives and alumni programs, and multi-channel diplomacy orchestras. The targeted implementation of the agenda has the potential to convert Ausbildung mobility into sustainable brain gain and balance partnerships.